Hormonal Therapy for Infantile Spasms: A Systematic Review and Meta-Analysis - Guang, Shiqi; Mao, Leilei; Zhong, Linxiu; Liu, Fangyun; Pan, Zou; Yin, Fei; Peng, Jing (Frontiers in Neurology, 2022)
Objective Limitations of adrenocorticotrophic hormone (ACTH) treatment for infantile spasms (ISs), such as high costs, limited availability and adverse effects, make it necessary to explore whether corticosteroids are optimal alternatives. Many other compelling treatments have gone through trials due to suboptimal effectiveness of hormonal therapy. A systematic review and meta-analysis was performed to evaluate effectiveness and safety of hormonal therapy for patients with ISs. Methods EMBASE, MEDLINE, CENTRAL and online registers were searched through April 2021 for randomized controlled trials (RCTs). Results Nineteen RCTs (N = 1279) were included. There was no significant difference between oral corticosteroids and ACTH in electro-clinical response (RR = 0.85, 95% 0.41 – 1.76). Low-dose ACTH had similar effectiveness in electro-clinical response compared to usual-dose group (RR = 0.94, 95% CI 0.60 – 1.47), but conferred lower risk of adverse effects (RR = 1.71, 95% CI 1.08 – 2.71). ACTH was more beneficial in controlling spasms than vigabatrin (RR = 1.31, 95% CI 1.05 – 1.64) in patients without tuberous sclerosis complex (TSC). All RCTs were connected through network meta-analysis, and we found ketogenic diet, zonisamide and methylprednisolone, and combined treatment of hormonal therapy with topiramate or pyridoxine, were not different compared to usual-dose ACTH. Conclusion Our analysis showed oral corticosteroids could be optional alternatives when ACTH is not applicable, and ACTH is more beneficial for patients without TSC. Moreover, low-dose ACTH is recommended due to comparable effectiveness but lower risks of adverse effects. However, due to high heterogeneity of included patients and treatment protocols, these results must be interpreted with caution. RCTs with multicentric involvement and larger sample size are needed for solid evaluation of other alternative treatments.